2017
DOI: 10.1111/jav.01132
|View full text |Cite
|
Sign up to set email alerts
|

Breeding limits foraging time: evidence of interrupted foraging response from body mass variation in a tropical environment

Abstract: Birds should store body reserves if starvation risk is anticipated; this is known as an 'interrupted foraging response'. If foraging remains unrestricted, however, body mass should remain low to limit the predation risk that gaining and carrying body reserves entails. In temperate environments mass gain in female birds during breeding is often attributed to egg formation and mass loss after incubation to flight adaptation or the effect of reproductive workload, rather than as a result of an adaptive interrupte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…But lower haptoglobin concentration cannot be interpreted as an overall down‐regulation of immune function in breeding birds, because ovotransferrin and nitric oxide concentrations, and haemolysis titre were higher in breeding birds and haemagglutination titre was not affected by breeding state. Note however, that in a diet manipulation experiment on Common Bulbuls, we observed that low haemolysis titre and high haptoglobin concentration are associated with loss of body mass (C. J. Nwaogu, A. Galema, W. Cresswell, M. W. Dietz, & B. I. Tieleman, unpublished data), and breeding Common Bulbuls are more likely to be in better condition (Nwaogu et al., ), so high haemolysis titre and low haptoglobin concentration may indicate less challenge. Similarly, incubating Common Eiders Somateria millissima in better body condition have higher NO x concentration (Bourgeon, Raclot, Le Maho, Ricquier, & Criscuolo, ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…But lower haptoglobin concentration cannot be interpreted as an overall down‐regulation of immune function in breeding birds, because ovotransferrin and nitric oxide concentrations, and haemolysis titre were higher in breeding birds and haemagglutination titre was not affected by breeding state. Note however, that in a diet manipulation experiment on Common Bulbuls, we observed that low haemolysis titre and high haptoglobin concentration are associated with loss of body mass (C. J. Nwaogu, A. Galema, W. Cresswell, M. W. Dietz, & B. I. Tieleman, unpublished data), and breeding Common Bulbuls are more likely to be in better condition (Nwaogu et al., ), so high haemolysis titre and low haptoglobin concentration may indicate less challenge. Similarly, incubating Common Eiders Somateria millissima in better body condition have higher NO x concentration (Bourgeon, Raclot, Le Maho, Ricquier, & Criscuolo, ).…”
Section: Discussionmentioning
confidence: 86%
“…In Nigeria, there is a single wet and dry season annually, and environmental factors differ between and within these seasons. Food is usually more abundant in the wet season (Ngozi Molokwu, Olsson, Nilsson, & Ottosson, ; Nwaogu, Dietz, Tieleman, & Cresswell, ), but pathogens and disease vectors should also be more abundant in the wet season due to high environmental productivity (Pascual, Bouma, & Dobson, ; Young, Garvin, & McDonald, ). However, social contact may increase with less food and water during the dry season because animals cluster around fewer resources, and this may facilitate disease transmission (VanderWaal, Gilbertson, Okanga, Allan, & Craft, ), even if pathogen abundance is low.…”
Section: Introductionmentioning
confidence: 99%
“…Tarsus length (in mm, which represents body size) and time of capture (linear and quadratic) were included as explanatory variables and bird identity and year as random variables. Body mass (g) with body size as covariate was used as a proxy of individual body reserves (as Nwaogu, Dietz, Tieleman, & Cresswell, 2017); we also tested body mass alone (without tarsus as covariate) and a "scaled body mass index" (Peig & Green, 2009), which produced qualitatively similar results (details in Table S2). intervals up to 24 weeks for rainfall and up to 32 weeks for temperature.…”
Section: Individual Body Condition To Test How Climate Variation Affmentioning
confidence: 96%
“…Specifically, E i is the basic energy reserve and cxt r is the product of the number of offspring produced in each breeding attempt (i.e., the clutch size) (c), the cost per offspring (x), and the time required for breeding successfully (t r ). Hence, the amount of energy and time required to commence breeding are positively correlated to clutch size (e.g., Eden, Horn, & Leonard, 1989;Møller, 2007;Nwaogu, Dietz, Tieleman, & Cresswell, 2017;Smith, Källander, & Nilsson, 1987). For simplicity, we also assume that clutch size is a fixed strategy and remains the same for each individual in each nesting attempt (see Supporting Information Figure S1 for reducing clutch size throughout the season).…”
Section: Model Overview and The Individual-based Modelmentioning
confidence: 99%